2018
DOI: 10.1039/c8qo00211h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic asymmetric 1,6-conjugate addition of in situ generated para-quinone methides with tritylthiol

Abstract: An asymmetric phase-transfer catalyzed 1,6-conjugate addition of in situ generated para-quinone methides with tritylthiol has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…20 In this context, 1,6-Michael addition reactions with carbon, phosphorus, and nitrogencentered nucleophiles were well-demonstrated in the p-QMs system in the presence of different catalysts and bases. 21 In the case of sulfur nucleophiles, chiral phosphoric acid-catalyzed enantioselective addition of thioacetic acid, 22 chiral phasetransfer catalyst-promoted asymmetric addition of tritylthiol, 23 triflic acid-catalyzed addition of thiols, 24 and sulfuric acidphosphine-promoted regioselective thiolation of p-QMs with sulfinates 25 were reported. However, the 1,6-addition of dithiocarbamic acid to p-QMs is not yet investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 In this context, 1,6-Michael addition reactions with carbon, phosphorus, and nitrogencentered nucleophiles were well-demonstrated in the p-QMs system in the presence of different catalysts and bases. 21 In the case of sulfur nucleophiles, chiral phosphoric acid-catalyzed enantioselective addition of thioacetic acid, 22 chiral phasetransfer catalyst-promoted asymmetric addition of tritylthiol, 23 triflic acid-catalyzed addition of thiols, 24 and sulfuric acidphosphine-promoted regioselective thiolation of p-QMs with sulfinates 25 were reported. However, the 1,6-addition of dithiocarbamic acid to p-QMs is not yet investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Li and co‐workers reported an enantioselective 1,6‐conjugate addition of tritylthiol 13 to prochiral para ‐quinone methides generated in situ from 4‐hydroxybenzyl p ‐tolyl sulfones 12 using chiral phase‐transfer catalyst ( S )‐ 15 (Scheme 3). [17,18] The reaction that was carried out in the presence of a saturated aqueous solution of Na 2 CO 3 afforded a range of enantioenriched α‐substituted benzyl thioethers 14 in high yields with high enantioselectivities. Racemic α‐substituted sulfones having electron‐deficient aryl groups, such as 4‐CF 3 C 6 H 4 and 2‐CF 3 C 6 H 4 , which are usually difficult to use in acidic conditions, could be successfully employed in this reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…However, in situ generation of p -QM from the corresponding phenol has also been also reported, in which case enantioselective reactions require substituents at the 2- and 6- positions. 10 …”
mentioning
confidence: 99%
“…We started our studies by selecting sulfone 1a as the model substrate to generate the corresponding aza- p -QM precursor (Table ). While the majority of reports makes use of amino alcohols as substrate to generate QM, , we found that in our case these compounds are quite unstable if the N atom is not protected, and therefore not suitable for catalysis.…”
mentioning
confidence: 99%